2021
DOI: 10.3390/ijerph18052463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation Combined with Exercises versus an Exercise Program on the Physical Characteristics and Functions of the Elderly: A Randomized Controlled Trial

Abstract: (1) Background—The application of neuromuscular electrical stimulation (NMES) combined with low-intensity exercise to the elderly can be more efficient than low-intensity exercise only in terms of delaying the loss of muscle mass. We aimed to assess the adjunct of NMES to low-intensity lower limb strengthening exercise to prevent falls in frail elderly for a relatively short period of 4 weeks. (2) Methods—Thirty elderly women aged 65 or above were randomly categorized into three groups: control group (CON, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
6
1
1
Order By: Relevance
“…Intriguingly, the combination of NMES on one leg and EX on the other leg resulted in a higher gene activation on each of the legs as compared to the groups that had unilateral intervention, suggesting synergetic effects. Previous studies have shown that NMES and EX at the same time, in the same leg with the same muscle, results in a greater muscle strengthening effect than EX alone 7,10,26,69,70 . Interestingly, this study demonstrated that the NMES and EX can potentiate each other even when performed in opposite extremities.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Intriguingly, the combination of NMES on one leg and EX on the other leg resulted in a higher gene activation on each of the legs as compared to the groups that had unilateral intervention, suggesting synergetic effects. Previous studies have shown that NMES and EX at the same time, in the same leg with the same muscle, results in a greater muscle strengthening effect than EX alone 7,10,26,69,70 . Interestingly, this study demonstrated that the NMES and EX can potentiate each other even when performed in opposite extremities.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have that NMES and EX at the same time, in the same leg with the same muscle, results in a greater muscle strengthening effect than EX alone. 7,10,26,69,70 Interestingly, this study demonstrated that the NMES and EX can potentiate each other even when performed in opposite extremities. These observations suggest involvement of either systemic hormonal mechanisms and/or effects mediated through the central nervous system, for example, recruitment and activation of additional motor units.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, hypothesis 2 is only partially confirmed, because the group’s performance on the iTUG did not change statistically significantly over the intervention period. In the study by Jang and Park ( 2021 ), the TUG performance of the group that only did strengthening exercises did not significantly improve after 4 weeks of intervention, but the group that additionally received NMES needed significantly less time to complete the test. These results are different from ours, probably because the NMES protocol and CTP program used by Jang and Park ( 2021 ) were different from those we used and because their intervention ended after 4 weeks.…”
Section: Discussionmentioning
confidence: 92%
“…The test was repeated thrice with a 1-min rest between the tests, and the average time was used for further analysis. Excellent test-retest reliability was represented in older adults (ICC = 0.99) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%